Analysis of Students Speaking Learning Needs in English for Marketing Courses - Citra Kusumaningsih; Finny Anita (IKIP PGRI Pontianak, 2021)
This research objectives are finding the target needs and learning needs of students who joined into English for marketing class. This research used mixed approach, namely quantitative and descriptive qualitative. The subject of this research is sixth semester students of English education study program who joined into English for marketing class. Data was collected from questionnaire and interview, it would be classified in order to get the information about what students’ need for speaking skills in English for marketing class. Based on the data revealed that English education study program and also the lecturers who taught the course are still needed to pay their attention to teaching materials for this course, especially for students’. Teaching materials speaking skills about marketing terms. Then, the students also stated they needed extended speaking for English marketing materials in order to help them improving students’ speaking skills, mean while based on the data revealed questionnaire and interview, the lecturers need to explore the teaching techniques and many other sources, it is for helping student’s competences on speaking skills for marketing.